Juergen's Model Approach to the Manufacturing Process for Th(3.77xz+DSr(1.77yz)) Nano Materials at 688.12 MHz per Tesla in a French CERN Cyclotron for Formation of a New Nuclear Fuels 1.09 TeV - Moh. Hardiyanto; Ermawati, Imas Ratna; Nathalia Gabiola Ganotti (Universitas Mandiri, 2024)
Continuous experiments carried out by the International Research Team in the Nano Materials Manufacturing Division which is a sub research of the ALICE Project were carried out at the Betha Group CERN, Lyon, France, an experimental project, one of which aims to determine the type and durability of nuclear nano materials based on Thorium Differentiation Hybrid Matrix based on nuclear hybrid Th (3.77) pairwise sub atomic Muon-Hadron particles with respect to the longitudinal angle function (xz) Deuterium Srontium (DSr) multi group tensoris (1.77yz) for an experimental series in a 687.12 MHz per tesla powering on Super-Gyro Magnetic field, in a series of super magnetic panels of the CERN Cyclotron coil in France with a quantum plasmatic frequency ranging from 901.44 MeV to 1.09 TeV with an azimuth angle range of 31.58 degrees cosine factor and 42.11 degrees tangential vectoric factor. The type of nano material that has undergone a series of verification tests based on the Juergen’s Model at its quantum polarization of 314.55 tesla per currie succeeded in producing the type Th(3.77xz+DSr(1.77yz)) with the breakthrough effect of Kaon atomic sub particles through the Josephson approximation. The multi level quantum plasmatic graduation has succeeded in achieving a sub atomic Electrical Conductivity (EC) value of 1.089 currie per MHz, so that it can be continued as the basis for the formation of new nuclear fuels with a power of 1.09 TeV at various angles of the CERN Cyclotron, in particular 39.72 degrees tensoris per MHz per azimuth.